An experiment implementation of a rule governed response - Moller, Joanne L. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The purpose of the present research was to investigate an instance of rule- governed behavior as discussed by Skinner (1969). A rule-governed response was brought under experimental control and the effect of positive reinforcement on the S use of the rule was assessed. The S was asked to either press a key and release it at his own pace or to press it and hold it for an estimated interval of ten seconds. The former response comprised the free-operant response mode and the later was the rule-governed response mode. The rule stated that the S could raise his probability of obtaining reinforcement by using this mode.